"Kekerasan Perempuan" dalam Tayangan Iklan Televisi Swasta Suatu Studi Lintas Budaya - Budianto, Irmayanti M. (Wacana, Journal of the Humanities of Indonesia, 2003)
This study reveals that some models of comercial breaks appeared at the Indonesian private television program, e.g. shampoo and soap advertisement, could invite some interpretation and functions. Their appearance could reflect women's surrender facing the action of violence. These article discusses about the metaphor of the women's body and how it becomes a medium that is constructed by two aspects, the power and the beauty. The result shows that the messages of comercial break gave meaningfulness of the pragmatical values, the persuasive or ideological statement and the dialectically comunicative process. Keywords appeared in the comercial breaks show the women's action of violence, pragmatical value, ideological value, dialectically communicative process.